2008
DOI: 10.1038/sj.mt.6300365
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Nucleolin Serves as Receptor for DNA Nanoparticles Composed of Pegylated Polylysine and DNA

Abstract: Compacted DNA nanoparticles deliver transgenes efficiently to the lung following intrapulmonary dosing. Here we show that nucleolin, a protein known to shuttle between the nucleus, cytoplasm, and cell surface, is a receptor for DNA nanoparticles at the cell surface. By using surface plasmon resonance (SPR), we demonstrate that nucleolin binds to DNA nanoparticles directly. The presence of nucleolin on the surface of HeLa and 16HBEo- cells was confirmed by surface biotinylation assay and immunofluorescence. Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 27 publications
4
113
0
Order By: Relevance
“…Although the plasmid dose received by the NP group was only B20% less, it has been argued that the markedly reduced inflammation in response to instillation of NP in the mouse lung is due to the pDNA within the NP formulation being masked from the toll-like receptor 9 in the endosome, 18 as a consequence of a nucleolin-mediated route of entry to the cell and into the nucleus. 29 Despite this, a modest BAL neutrophil response has been reported for a 100 mg dose administered to the lungs of Balb/c mice, 18 which could be consistent with the trend towards increased BAL neutrophils observed after lung delivery in the sheep.…”
Section: Evaluation Of Non-viral Gtas In the Ovine Lung G Mclachlan Ementioning
confidence: 65%
“…Although the plasmid dose received by the NP group was only B20% less, it has been argued that the markedly reduced inflammation in response to instillation of NP in the mouse lung is due to the pDNA within the NP formulation being masked from the toll-like receptor 9 in the endosome, 18 as a consequence of a nucleolin-mediated route of entry to the cell and into the nucleus. 29 Despite this, a modest BAL neutrophil response has been reported for a 100 mg dose administered to the lungs of Balb/c mice, 18 which could be consistent with the trend towards increased BAL neutrophils observed after lung delivery in the sheep.…”
Section: Evaluation Of Non-viral Gtas In the Ovine Lung G Mclachlan Ementioning
confidence: 65%
“…However, it is also possible that KLF4 may be migrated to cell surface under overexpression conditions. Recent studies showed that nucleolin, a nuclear protein, was present on the surface of various cell types, despite lacking a transmembrane domain or a signal sequence (24,25). Therefore, nucleolin acts as a receptor on plasma membrane and shuttles the ligand from the plasma membrane to the cytoplasm and nucleus (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Cleveland-based Copernicus Therapeutics, Inc. developed a compacted DNA/DNA nanoparticle therapy (PLASmin ® ) that decreases the volume of the complex by up to 1000-fold, to a single molecule small enough to permeate the membrane and nuclei of target cells. The complex contains only one copy of the DNA to be delivered, increasing the stability and efficacy of the treatment (Chen et al, 2007). In phase 1a trials, plasmid DNA nanoparticles with the gene responsible for encoding CFTR were applied intra-nasally with lysine peptides substituted with polyethylene glycol.…”
Section: Anti-inflammatoriesmentioning
confidence: 99%